Congenital anomalies in fetus during pregnancy-predisposing factor and management in rural set up - Patil, Sunil Somnath; Pardeshi, Punam Bhimsing; Sambarey, Pradip Wamnrao (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Congenital anomalies are the vital causes for perinatal mortality and morbidity. Therefore, an antenatal diagnosis and foetal therapy have attained importance in the field of human embryology. Methods: This was an observational study conducted in antenatal, labour and postnatal ward at Rural medical college and hospital for 2 years. The aim of study is to review the overall frequency of congenital malformation and to increase public awareness in saving newborns from birth defects. Results: Cause of congenital anomalies was unknown in 82.1% of the cases in our study. Out of 162 congenital anomalies 60.49% were antenataly registered whereas 39.51% were unregistered. Most common system involved in congenital anomaly was Central nervous system (CNS) followed by gastrointestinal anomaly. In central nervous system anencephaly was commonest abnormality. sensitivity of ultrasonography was 74.03% and specificity was 98.86%. Conclusions: Every mother should undergo early anomaly. Fortification of food with iron, folic acid, iodine should be carried out. Anemia should be tackled early in reproductive age group. Maternal perinatal infection can be prevented through vaccination and if identified, diagnosed and treated early, would also help in decreasing congenital anomalies in baby.